Balancing the strength and ductility of Mg-6Zn-0.2Ca alloy via sub-rapid solidification combined with hard-plate rolling. (10th August 2021) - Jin, Zhong-Zheng; Zha, Min; Jia, Hai-Long; Ma, Pin-Kui; Wang, Si-Qing; Liang, Jia-Wei; Wang, Hui-Yuan
Graphical abstract: Highlights: SRS combined with HPR allows for a Mg-6Zn-0.2Ca alloy having a superior combination of ductility and strength. Refined and dispersed eutectic phase introduced by SRS and HPR could effectively alleviate or avoid the crack initiation. Excessive Ca solute atoms in α-Mg matrix result in the yield point phenomenon and enhanced strain-hardening ability. Abstract: In this study, we successfully prepared a Mg-6Zn-0.2Ca alloy by utilizing sub-rapid solidification (SRS) combined with hard-plate rolling (HPR), whose elongation-to-failure increases from ∼17 % to ∼23 % without sacrificing tensile strength (∼290 MPa) compared with its counterpart processed via conventional solidification (CS) followed by HPR. Notably, both samples feature a similar refined grain structure with an average grain size of ∼2.1 and ∼2.5 μm, respectively. However, the high cooling rate of ∼150 K/s introduced by SRS modified both the size and morphology of Ca2 Mg6 Zn3 eutectic phase in comparison to those coarse ones under CS condition. By subsequent HPR, the Ca2 Mg6 Zn3 phase was further refined and dispersed uniformly by severe fragmentation. Specially, the achieved supersaturation containing excessive Ca solute atoms due to high cooling rate was maintained in the SRS-HPR condition. The mechanisms that govern the high ductility of the SRS-HPR sample could be ascribed to following reasons. First, refined Ca2 Mg6 Zn3 eutectic phase could effectively alleviate or avoid the crack initiation. Furthermore, excessive Ca solute atoms in α-Mg matrix result in the yield point phenomenon and enhanced strain-hardening ability during tension. The findings proposed a short-processed strategy towards superior performance of Mg-6Zn-0.2Ca alloy for industrial applications.